AB1062 Risk factors for mortality after tuberculous arthritis. (12th June 2018) - Chen, Y.-C.
Abstract : Background: Tuberculosis arthritis is an emerging international problem despite advances in the methods of diagnosis and treatment; it is still prevalent in developing countries and on the increase in developed ones. Objectives: Patients with tuberculous (TB) arthritis increase mortality This study investigated to search for the risk factors of mortality in TB arthritis. Methods: We retrospectively reviewed patients with TB arthritis who admit to Kaohsiung Chang Gang Memorial Hospital Jauary 2001 to December 2015. The long-term outcomes of the patients were analysed. Results: A total of 281 patients (124 females and 17 males; mean age: 64.86±14.51 years) were enrolled. At the end of the study, 229 patients were alive and 52 had died. The mean follow up period were 8.31±4.52 years. The patients who were old age (p=0.004, HR=1.038, 95% CI 1.012–1.065), liver disease (p=0.036, HR=2.571, 95% CI 1.062–6.224) and underlying cancer (p=0.001, HR=3.640, 95% CI 1.725–7.679) had a significantly higher mortality rate than others. Conclusions: When we treat TB arthritis, old age and underlying liver and cancer history should paid more attention to decrease the risk of mortality. Reference: [1] LongQ, LiY, WangYetal(2008)BarrierstoaccessingTBdiagnosis forrural-to-urbanmigrantswithchroniccoughinChongqing, China: a mixed methods study. BMC Health Serv Res8:202 Acknowledgements: We thank Kaohsiung CGMH for data support Disclosure of Interest: None declared